2015
DOI: 10.2169/internalmedicine.54.2292
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mediastinitis due to Methicillin-resistant Staphylococcus aureus in a Renal Dysfunction Patient Undergoing Adjustments to the Linezolid Dose

Abstract: This study is the first case report of the treatment of methicillin-resistant Staphylococcus aureus (MRSA) mediastinitis using therapeutic drug monitoring of the serum and wound exudate concentrations of linezolid in a renal dysfunction patient. In the present study, the serum trough concentration of linezolid was maintained between 2 and 7 μg/mL. Therapeutic drug monitoring dosage adjustments may be especially useful in patients with renal dysfunction and severe MRSA infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In the four youngest hospitalized patients (aged 1, 5, 8 and 13 years), RF was assumed to be 0.5. RF was included in the model, using a linear independent combination of renal and non-renal CL parameters, as shown in Equation (6). CL OVERALL is the overall population value of parameter for CL.…”
Section: Covariate Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In the four youngest hospitalized patients (aged 1, 5, 8 and 13 years), RF was assumed to be 0.5. RF was included in the model, using a linear independent combination of renal and non-renal CL parameters, as shown in Equation (6). CL OVERALL is the overall population value of parameter for CL.…”
Section: Covariate Modelmentioning
confidence: 99%
“…Linezolid is a member of the oxazolidinone class of synthetic antimicrobial agents with a unique mechanism action compared with other agents in this class . It has been used to treat critical infections, including pneumonia, sepsis, and wound, skin and soft tissue infections . It has strong antibacterial activity against aerobic Gram‐positive cocci (GPC), methicillin‐resistant coagulase‐negative staphylococci, vancomycin‐resistant enterococci and methicillin‐resistant Staphylococcus aureus (MRSA) , and has been approved for use in more than 60 countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brier et al showed approximately 30% -50% of the administered dose of the drug was removed by hemodialysis, but hemodialysis patients had the higher concentration of linezolid than that of non-hemodialysis patients [10]. Despite of the decreasing daily dose of linezolid from 1200 to 600 mg at the start of treatment to prevent thrombocytopenia in a renal dysfunction patient, the concentration of linezolid in the serum was 11.5 μg/mL on 21st day of linezolid therapy, which was sufficient to induce thrombocytopenia [11]. Additionally, they reported that linezolid concentration was similar between the wound exudate and serum [11].…”
Section: Discussionmentioning
confidence: 96%
“…Despite of the decreasing daily dose of linezolid from 1200 to 600 mg at the start of treatment to prevent thrombocytopenia in a renal dysfunction patient, the concentration of linezolid in the serum was 11.5 μg/mL on 21st day of linezolid therapy, which was sufficient to induce thrombocytopenia [11]. Additionally, they reported that linezolid concentration was similar between the wound exudate and serum [11]. Therefore, we thought that thrombocytopenia in hemodialysis patients was associated with the accumulation of linezolid.…”
Section: Discussionmentioning
confidence: 97%